Just last night ebook A novel. - McFarlane, Mhairi (2021)
"I cannot remember the last book I loved as much... a luminous, heart-achingly beautiful love letter to friendship. Knockout!" — Josie Silver, New York Times bestselling author International bestseller Mhairi McFarlane explores lifelong friendships, long-buried secrets, and unexpected love in a heartfelt, emotional new novel, perfect for fans of Evvie Drake Starts Over, The Two Lives of Lydia Bird, or In Five Years. Eve, Justin, Susie, and Ed have been friends since they were teenagers. Now in their thirties, the four are as close as ever, Thursday night bar trivia is sacred, and Eve is still secretly in love with Ed. Maybe she should have moved on by now, but she can't stop thinking about what could have been. And she knows Ed still thinks about it, too. But then, in an instant, their lives are changed forever. In the aftermath, Eve's world is upended. As stunning secrets are revealed, she begins to wonder if she really knew her friends as well as she thought. And when someone from the past comes back into her life, Eve's future veers in a surprising new direction... They say every love story starts with a single moment. What if it was just last night? "[A] book I almost wish I'd written, except that would have robbed me of the intense joy of reading it... the kind of novel that will have you putting everything else on hold so you can keep turning pages until you reach its sparkling, brilliant end." — Emily Henry, #1 New York Times bestselling author of People We Meet on Vacation